Mediating roles of organizational learning and knowledge creation process in the relationship between human resource management practices and organization performance improvement - Elangkovan Narayanan Alagas, (2014)
The general recognition from literatures is that human resource management practices improve organizational performance. One possible explanation is that a human resource management practice does not have direct effect on organizational performance improvement, but an indirect effect by improving organizational outcomes. This study suggest that organizational learning and knowledge creation process mediates the relationship between human resource management practices and organizational performance improvement and that adoption of human resource management practices enhance performance through its positive effect on organizational learning and knowledge creation process. Organizational learning and knowledge creation process has become to be considered as valuable assets that can provide proprietary for performance improvement. The foundation of organizational learning and the knowledge creation process is needed as an important link to establish organizational performance improvement. Past studies have been elusive on the strength of the relationship between these variables. The study of organizational learning and the knowledge creation process not only serve as an important link but have created a gap in the body of knowledge in terms of theoretical and practical aspect for organizational performance improvement. Using the theory of action perspective, social learning theory, organizational knowledge creation process and resource based view; a quantitative research was carried to achieve the research objectives by examining the relationship between human resource management practices and the mediation effect of organizational learning and knowledge creation process on organizational performance improvement in the private higher educational institutions. Thus in general the study examined the current perceived level of human resource management practices, organizational learning, knowledge creation process and organizational performance improvement in the private higher educational institutions. This study was conducted among private higher educational institutions in Klang Valley,Negeri Sembilan, Melaka and Perak. A total of 362 responded with complete questionnaires (31.1% response rate). Based on the Structural Equation Modeling (SEM) approach this research revealed that there is a significant positive and a linear relationship between human resource management practices, organizational learning,knowledge creation process and organizational performance improvement. In addition,there is a significant positive relationship between organizational learning and knowledge creation process on organizational performance improvement. SEM was conducted based on the bootstrap method on organizational learning and knowledge creation process to test the mediation effect. The result illustrates that organizational learning and knowledge creation process partially mediates human resource management practices and organizational performance improvement. Generally the study managed to provide empirical evidence and support on the perception of private higher educational institutions on the issue of organizational learning and the knowledge creation process. This study will add to the existing literature and provide useful foundation in the field of organizational learning and knowledge creation process in the field of theory of action perspective for organizational learning and dynamic theory of organizational knowledge creation for knowledge creation process. For practitioners this study could help private higher educational institutions to create new knowledge and implement effective learning process to enhance performance improvement. For policy makers the study will enhance to create a new pathway of achieving educational excellence in the country. For future recommendations, this study could focus on longitudinal study and also should consider triangulation to employ both qualitative and quantitative approach, which may provide more quality data to enrich the understanding of organizational learning and knowledge creation process to enhance performance improvement. In conclusion, the results implied that, organizational learning and knowledge creation process serve as an important driver for academics, administrators and practitioners to encourage and establish organizational learning process and knowledge creation process to create and develop intellectual capital that will enhance private higher educational institutions to achieve greater performance improvement.